Pulsed high magnetic field-induced reversible blood-brain barrier permeability to enhance brain-targeted drug delivery. (3rd July 2021) - Heydarheydari, Sahel; Firoozabadi, Seyed Mohammad; Mirnajafi-Zadeh, Javad; Shankayi, Zeinab
ABSTRACT: The present study aimed to select an effective Pulsed High Magnetic Field (PHMF) stimulation protocol that would induce the Blood-Brain Barrier's (BBB) reversible permeability to enhance brain-targeted drug delivery. PHMF was applied to the skull over the right hemisphere of 60 Wistar rats. The sham group contained other 10 rats that did not receive PHMF stimulation. The investigated parameters were repetition frequencies (0.25, 1, and 4 Hz as well as the effective low frequency combined with 10 Hz) and numbers of pulses in each train. Evans Blue Dye (EBD) uptake within the brain parenchyma was measured to select an effective PHMF stimulation protocol. BBB reversibility was evaluated by measuring EBD uptake and Gadobutrol retention, through MRI signal intensity enhancement, within brain parenchyma after exposure to the effective PHMF stimulation protocol at different time points including 0.5, 1, and 24 hours. The obtained results showed that the PHMF stimulation increased the BBB's reversible permeability; this increase was more significant for 28 pulses with 1 Hz frequency ( P < .0001). Changes in EBD uptake and MRI signal intensity in the exposed side (right hemisphere) peaked within 0.5–1 hour and returned to normal levels 24 hours after exposure to the effective protocol of PHMF stimulation (28 pulses with 1 Hz frequency). The Contrast-Enhanced MRI (CE-MRI) signal intensity confirmed the changes in EBD concentration. PHMF stimulation can be used as an effective protocol for enhancing the permeability reversibly of BBB, hence considered a potential clinical approach to brain-targeted drug delivery.